Muzzling communication: sedition law as a tool to manage ethnic relations - Shuaib, Farid Sufian (Sweet & Maxwell Asia, 2009)
Multi-ethnic and multi-religious make up of Malaysian society requires a deft hand in managing ethnic relation. Malaysia has a history of ethnic relations flare-ups such as the May 13 incident in 1969. One of the causes attributed to the incident was unruly speeches that incited inter-ethnic hatred. Apart from social and economic policies and action-plans, laws regarding speech could also be used as a tool to prevent such incidents. Sedition law is one of the legislation to suppress speeches that may incite violence between ethnic groups. The law has been used in a number of incidents including political speeches that tend to cause ill-feeling and hostility between ethnic groups. The courts have also decided in several cases to punish writers of seditious publication. However, there were also criticisms of abuse of sedition law in suppressing or inhibiting dissent against the government of the day. After 60 years of the Sedition Act 1948, it is timely to consider its usefulness and efficacy in managing ethnic relations. This paper seeks to analyse the use and abuse of sedition law by looking at legislation and judgement of the courts. The paper will also consider whether there is a better legislative scheme to do the job of managing ethnic relation.